PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP LOYALITAS PELANGGAN PADA PRODUK ICHIOCHA DI PT INDOMARCO ADI PRIMA KEDIRI - Bhondan Eko Satriyo; Sri Wahyuni Mega; Lina Saptaria (CV SWA Anugrah, 2023)
This research aims to determine the influence of product quality and brand image on customer loyalty to Ichiocha products at PT Indomarco Adi Prima Kediri. The variables in this research are Product Quality (X1), Brand Image (X2), and Customer Loyalty (Y). This research uses quantitative methods using data collection techniques in the form of interviews, observations, literature studies and questionnaires. Meanwhile, the analysis used is validity test, reliability test, classical assumption test, multiple linear regression test, t test and f test and coefficient of determination. Sampling in this research used purposive sampling considering that PT Indomarco Adi Prima Kediri's consumers were 85 people based on the results of the research conducted. The results of this research used the SPSS 25.0 program using a significance level of 5% or 0.05 with results (1) The results of the t test calculation on the first hypothesis obtained a calculated t value of 1.184 with a significance value of 0.013 < 0.05. These results indicate that Ha is accepted and Ho is rejected, meaning that there is a partial influence between product quality variables on consumer loyalty at PT Adi Prima Tulungagung. (2) The results of the t test calculation on the second hypothesis obtained a calculated t value of 3.514 with a significance value of 0.021 < 0.05. These results show that Ha is accepted and Ho is rejected, meaning that there is a partial influence between the brand image variable on consumer loyalty at PT Adi Prima Tulungagung. (3) The calculated F value in this study was 9.325 and the F significance value was 0.000, which is <0.05. It can be concluded that Ha is accepted and Ho is rejected, which means that product quality and brand image simultaneously have a significant effect on consumer loyalty at PT Adi Prima Tulungagung. These results prove that empirically the third hypothesis can be proven.